How Fear and Stress Shape the Mind - Luke R. Johnson (Frontiers Research Topics, 2016)
The experience of fear and stress leaves an indelible trace on the brain. This indelible trace is observed as both changes in behavior and changes in neuronal structure and function. Fear and stress interact on many levels. The experience of stress may lead to the formation of a fearful memory trace of a place or reminder cue, and fearful memory formation is regulated by the extent of concurrent stress. The concurrent experience of fear and stress may amplify fear and slow fear extinction which may lead to pathology. Fear memory formation involves changes in synaptic plasticity while stress and glucocorticoids change neuronal structure. Thus, both neurons and synapses are changed. These changes can be identified, visualised and mapped within focused microcircuits. In this Research Topic we focus on current advances in both the neurobiology and behavioral consequences of fear and stress.